Effectiveness of Physical Activity in Geriatric Population to Decrease the Risk of Fall a Randomized Control Trial - Muhammad Adnan, Huda Anjum, Hadiqa Adnan, Hafiza Sabeen Ayesha, Wajeeha Alam, Sana Umar, Saman Jahangir, Bismah Ashraf, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: For elderly persons who are frail, effective fall prevention strategies are required. Our goal was to evaluate physical activity's value in preventing falls in older persons. Material and Methodology: The physiological profile evaluation was used to conduct a randomised control experiment on individuals aged sixty five and older who were categorised as pre-frail and had mild to moderate fall risk scores.A total of 54 participants were recruited in the study using allocation concealment. 54 participants were split into two groups at random i.e MPE (n = 27), control (n = 27). The three-day-per-week, 12-week intervention mainly concentrated on proprioception, muscular development, response time, and balancing training. The main finding was the assessment of fall risk using PPA twelve weeks after baseline and at a 24 week follow-up. Results: At weeks 12 and 24, there were significant changes between the MPE group and controls in the fall risk, proprioception, muscle strength, response speed, postural sway, and fear of falling scores. In addition, the MPE group's HRQOL had dramatically improved compared to controls. Practical Implication: by identifying and establishing effect of physical activity in geriatric population in reducing risk of fall, clinical phrophylatic and rehabilitation palns can be designed and implemented before hand to decrease the chances of fall iniuries and to facilitate the rehabilitation plan after the injury. Conclusion: The MPE programme significantly improved proprioception, response time, and postural sway in elderly people with pre-frailty, which decreased the risk of falls.The MPE programme is therefore advised for use in routine primary care for the geriatric population. Keywords: Fall, Geriatric, MPE, Physical Activity, risk of fall, pre-frail, multiple physical exercise, HRQOL, postural sway